Vertical root fractures in endodontically-treated teeth: A retrospective analysis of possible risk factors (2018)
AIM: The prevalence of vertical root fractures (VRF) ranges from 2% to 20%, and is associated with endodontically-treated teeth (ETT). The aim of the present study was to analyze clinically and radiographically, at different intervals of time, some of the risk factors present in ETT that developed VRF.METHODS: A classification model according to time measured the follow-up period of three groups. A match was made for times of occurrence (cases) and follow up (controls). An odds ratio (OR) test and a logistic regression model set at 95% confidence interval (CI) established the VRF probability when different clinical factors (patient, tooth, and endodontic or restorative treatment) were present.RESULTS: The sample was composed of 197 ETT (41 cases and 156 controls). A classification model set the trend, thus defining three groups: group 1 (1-4 years of follow up): endodontic retreatment (OR: 8.01, 95% CI: 1.85-37.90, P=.0014), indirect restoration (OR: .202, 95% CI: .036-.979, P=.05); group 2 (5-8 years of follow up): primary treatment (OR: .052, 95% CI: .002-.680, P=.044) and the 'single tooth' category (OR: .042, 95% CI: .002-.453, P=.02) demonstrated a significant association with VRF; and group 3 (>9 years of follow up): no association.CONCLUSION: Endodontic retreatment had the highest risk association for VRF after 1-8 years of follow up. Indirect and individual restorations were not significantly associated with VRF. © 2017 John Wiley and Sons Australia, Ltd.